ChemInform Abstract: Two New Eupodienone Lignans from Gymnotheca chinensis. Issue 31 (5th August 2014) - Xiao, Shi‐Ji; Chen, Fang; Ding, Li‐Sheng; Zhou, Yan
Abstract isolation, structure elucidation and cytotoxicity of two new eupodienone lignans, gymnothelignan T (I) and gymnothelignan U (II)